Dosimetric Evaluation and Verification of External Beam 3-D Treatment Plans in Humanoid Phantom Using Thermoluminescent Dosimeters (TLDs) - Rizwana Siddique; Zaheer Uddin; Muzaffar Hussain (Journal of Basic & Applied Sciences, 2021)
Dosimetric Evaluation & Verification Of External Beam 3-D Treatment Plans In Humanoid Phantom have been carried out. In this study male anthromorphic phantom, model no.702 D, manufactured by Atom Ltd has been used. The plan was delivered to phantom and TLD- 100 was placed in cavities to evaluate and verify the dose delivered by implementing 3D treatment plans. TLD 100 was calibrated using SIEMENS PRIMUS PLUS Linear Accelerator with calibrated 6 MV X ray beam. We chose phantom skull, abdomen and pelvis region for making treatment plans and then doses by treatment plans have been verified by TLDs. 4%, 3.5% and 3% variation in the results was found for skull, pelvis and abdomen region respectively which is within the safe limit of accuracy i-e from 3% to 5 %. Before working with TLDs, it has also been found that thermoluminescent dosimeters were showing the linear response and results are reproducible for the dose range from 50 cGy to 200 cGy. This study has been performed at Karachi Institute of Radiotherapy and Nuclear Medicine (KIRAN) during the year 2010-2011.